Plasticity in cell migration modes across development, physiology, and disease - Pourjafar, Mona; Tiwari, Vijay K. (Frontiers in Cell and Developmental Biology, 2024)
Cell migration is fundamental to both development and adult physiology, including gastrulation, brain development, angiogenesis, wound healing, bone remodeling, tissue homeostasis, and the immune response. Additionally, misguided cellular migration is implicated in disease pathologies such as cancer metastasis and fibrosis. The microenvironment influences cell migration modes including mesenchymal, amoeboid, lobopodial, and collective, and these are governed through local signaling by affecting gene expression and epigenetic alteration of migration-related genes. A plasticity in switching between migration modes is essential for key cellular processes across various contexts. Understanding the mechanisms of cell migration modes is essential for unraveling the complexities of this process and revealing its implications in physiological and pathological contexts. This review focuses on different modes of cell migration, including their aberrant migration in disease pathologies and how they can be therapeutically targeted in disease conditions such as cancer.